Pembelajaran Bahasa Inggris Berbasis Pendidikan Non-Formal di Kampung Inggris Kediri - Saraka Saraka (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The purposes of this study are to explore non-formal teaching methods and perceptions on the non-formal settings for learning the English language in base-camp, café and examination to interact with English native speakers in Prambanan Temple. This study used a qualitative approach to assign a case study design. The study was conducted in Kampung Inggris Pare, Kediri, Indonesia in 5 weeks. A number of 30 respondents each of which 15 from AC course and 15 from CC course were selected. Of the 30 respondents, 10 were good English competence, 10 fair and 10 low. Data were analyzed using cultural thematic analysis, rate percentage, and frequency. Results show that non-formal education teaching methods are perceived by students as non-formal methods stressing in free classroom interactions and presentations. Of three sites of learning, students with good competence in English accept all as comfortable learning sites. In addition, maturity attitudes that include self-reliance, self-confidence, easy to adapt to the environment, and creativity are well performed by the students. Likewise, students with fair English competence considered camp, café and the temple at lower degrees. Maturity is also performed lower by the fair category students with the lowest degree at 60%. The low competence students, however, can receive camp only as a comfortable place to learning. All categories of maturity are performed in a low motion achieving 30% by the low competence students.